Patient’s assessment on quality of Obstetrics and Gynecology service at Dr. Cipto Mangunkusumo Hospital - Erni Nurrahmi Suprihatin Priatna (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To evaluate patient’s assessment on service quality of Obstetrics and Gynecology at Dr. Cipto Mangunkusumo Hospital, the importance of each service quality dimension, and the relation between quality assessment and several factors. Method: The research was performed to 112 patients who were hospitalized in the Obstetrics and Gynecology ward in August 2009. We used a questionnaire which was developed from SERVQUAL instrument. This questionnaire consists of 26 questions about patient expectation and perception on the service they received. It covered 5 service quality dimensions (reliability, responsiveness, assurance, empathy, and tangibility). Patients were asked to state the answer in Likert scale from 1 to 7. The gap between perception and expectation score was then calculated. If the gap was zero or positive it means the quality was good and if negative it means the quality was not good. Result: Among 112 respondents, 82 respondents (73.2%) assess that the service quality was not good, only 26.8% considered it good. Reliability dimension had the highest expectation score followed by assurance, responsiveness, empathy, and tangibility with the proportion of 21%, 20%, 20%, 20%, and 19% respectively. The sequence of the gap from the biggest to the smallest was empathy, responsiveness, reliability, assurance, and tangibility. There was a significant relationship between patients’ educational background and assessment of service quality (p=0.036). Conclusion: Obstetrics and Gynecology Deparment’s service quality at Dr. Cipto Mangunkusumo Hospital has not fulfilled patients’ expectation. Improvements of the service quality need to be addressed on 4 factors, which are empathy, reliability, responsiveness, and assurance. [Indones J Obstet Gynecol 2010; 34-2: 77-83] Keywords: patient expectation, patient perception, Obstetrics and Gynecology service quality